2007
DOI: 10.1183/09031936.00077106
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arteriovenous fistula in a patient with renal cell carcinoma

Abstract: Arteriovenous (AV) fistulas are common in renal cell carcinoma. These are usually small and asymptomatic. Case reports have previously described symptomatic fistulas in primary renal cell tumour or, less commonly, bone metastases.The current study describes a patient with lung metastases from renal cell carcinoma who developed a symptomatic pulmonary AV fistula. The patient presented with debilitating progressive shortness of breath, which resolved after coiling of the pulmonary AV fistula. Supporting radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It can also be caused by a variety of acquired disease, with the pathogenesis has not been fully elucidated. It was reported that some conditions can lead to the formation of PAVFs, such as blood metastatic in the lung of choriocarcinoma and renal cell carcinoma [ 14 , 15 ]. Less common concomitant diseases include penetrating chest trauma, mitral stenosis, schistosomiasis, actinomycosis, Fanconi syndrome, and metastatic thyroid cancer [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can also be caused by a variety of acquired disease, with the pathogenesis has not been fully elucidated. It was reported that some conditions can lead to the formation of PAVFs, such as blood metastatic in the lung of choriocarcinoma and renal cell carcinoma [ 14 , 15 ]. Less common concomitant diseases include penetrating chest trauma, mitral stenosis, schistosomiasis, actinomycosis, Fanconi syndrome, and metastatic thyroid cancer [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most pulmonary AV shunts are hereditary and noted in patients with hereditary hemorrhagic telangiectasia; however, enlarged acquired shunts may also be noted in patients with hepatopulmonary syndrome, malignancy, and schistosomiasis. 17,18 In addition to its use in lymphangiography, ethiodized oil is also used as a contrast agent in hysterosalpingography and is routinely used as an embolic agent in transarterial chemoembolization (TACE), most commonly for primary liver cancer. 19 There are multiple case reports of systemic embolization of ethiodized oil after these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This is the third case report of AV shunting from pulmonary metastases . There may be an increase in such presentations, given improvements in oncological care and extended survival in patients with vascular lung metastases.…”
mentioning
confidence: 82%